Application Of Activity Based Costing Method To Determine The Cost Of Production : Penerapan Metode Activity Based Costing Untuk Menentukan Harga Pokok Produksi - Ita Sri Mulyani; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2021)
To analyze the comparison of calculations with the Activity Based Costing Method. This research is designed as a descriptive analytical study, quantitative analysis, which is used in calculating the traditional method and the Activity Based Costing method, while qualitative analysis is used in analyzing the results of the two variables of the traditional method and the Activity Based Costing Method. detailed data in the form of production data during the current period. Based on the results of the analysis, both the Activity Based Costing Method resulted in lower costs. Therefore, the Activity Based Costing Method can be used as an alternative for companies in calculating the cost of goods manufactured which is good because this method is a method that calculates the real and detailed production costs.